Advertisement Remove all ads

X2 + X + 3 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

\[\frac{1}{\sqrt{3 - x}}\]

Advertisement Remove all ads

Solution

\[ \frac{d}{dx}\left( f(x) \right) = \lim_{h \to 0} \frac{f\left( x + h \right) - f\left( x \right)}{h}\]
\[ = \lim_{h \to 0} \frac{\frac{1}{\sqrt{3 - x - h}} - \frac{1}{\sqrt{3 - x}}}{h}\]
\[ = \lim_{h \to 0} \frac{\left( \sqrt{3 - x} - \sqrt{3 - x - h} \right)}{h\sqrt{3 - x}\sqrt{3 - x - h}}\]
\[ = \lim_{h \to 0} \frac{\left( \sqrt{3 - x} - \sqrt{3 - x - h} \right)}{h\sqrt{3 - x}\sqrt{3 - x - h}} \times \frac{\left( \sqrt{3 - x} + \sqrt{3 - x - h} \right)}{\left( \sqrt{3 - x} + \sqrt{3 - x - h} \right)}\]
\[ = \lim_{h \to 0} \frac{\left( 3 - x - 3 + x + h \right)}{h\sqrt{3 - x}\sqrt{3 - x - h}\left( \sqrt{3 - x} + \sqrt{3 - x - h} \right)}\]
\[ = \lim_{h \to 0} \frac{h}{h\sqrt{3 - x}\sqrt{3 - x - h}\left( \sqrt{3 - x} + \sqrt{3 - x - h} \right)}\]
\[ = \lim_{h \to 0} \frac{1}{\sqrt{3 - x}\sqrt{3 - x - h}\left( \sqrt{3 - x} + \sqrt{3 - x - h} \right)}\]
\[ = \frac{1}{\sqrt{3 - x}\sqrt{3 - x - 0}\left( \sqrt{3 - x} + \sqrt{3 - x - 0} \right)}\]
\[ = \frac{1}{\left( 3 - x \right) \left( 2\sqrt{3 - x} \right)}\]
\[ = \frac{1}{2 \left( 3 - x \right)^\frac{3}{2}}\]

Concept: The Concept of Derivative - Algebra of Derivative of Functions
  Is there an error in this question or solution?

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 30 Derivatives
Exercise 30.2 | Q 1.09 | Page 25

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×